Acting together An integrated account of joint action - Lindner, Nicolas (mentis Verlag, 2020)
Without joint action, man's cultural, scientific and everyday achievements would be unthinkable. What special cognitive abilities make it possible for this to happen so often and in so many ways? Dancing, waging war, building a castle together in the sandbox - joint action is a central component of everyday life and the success of mankind. This ability is based on special socio-cognitive abilities, the scope and interplay of which characterize the human species. Literature often focuses on the large and complex forms of joint action.This book represents an attempt to present a philosophical reconstruction of joint action through an interdisciplinary investigation of small forms with few actors. This is suitable for explaining the behavior of children and adults, as well as for taking into account empirical results from related disciplines, especially developmental psychology